Penciptaan motif batik kabumian sebagai ikon Kabupaten Kebumen - Khafis, Mohamad Syahrul; Murty, Daru Anggara; Sasongko, Aditya Dimas Wahyu (Canting : Jurnal Batik Indonesia, 2024)
Each region has local potential which is visualized in the form of art. However, there are several regions that do not yet have the characteristics of batik in that area. One of them is Kebumen Regency. Creating batik motifs inspired by natural potential and icons in Kebumen Regency, knowing how to visualize and how to apply them to written batik. Descriptive qualitative methods, with interviews, literature studies, observation, documentation and visual studies were used in this research. The research results show that after going through several exploration processes looking for existing potential, there are 5 sources of ideas used as the main motif, namely rice, coconut, swallows, boats, and shrimp. The batik cloth is made using the written batik technique and the dyeing process using the dyeing technique. The dyes used are indigosol o4b, ib, and 14r which are fixed using HCl and nitrite solutions. The results of this study, the batik made contains 5 elements that are the reference or icon of Kebumen Regency and in the future can become the characteristic batik of Kebumen Regency.